Microstructural analysis of asymmetric dilution by rotating direct metal deposition - Choi, Byungjoo; Lee, Gwang Jae; Yeom, Hyun Ho; Lee, Moon Gu; Jeon, Yongho (Archives of Metallurgy and Materials, 2019)
In this study, cross-section analysis was performed on a novel rotating direct-metal deposition method capable of preliminary surface treatment and damage repair of cylindrical inner walls. The cross-sectional shape, microstructure, and metallurgical composition were analyzed to verify feasibility. No defects such as porosity or cracks were found in the cross section, but asymmetric dilution was observed because of the non-coaxial powder nozzle. Microstructural coarsening was confirmed over a higher dilution area by high-magnification optical microscope images. As the dilution ratio was increased, hard carbides in the dendrite were bulkdiffused into inter-dendrite spaces, and the toughness was lowered by Fe penetration into the deposit. Therefore, the increased laser heat input can be modulated to the typical dilution by decreasing the laser scanning velocity.
Keywords: Cross sectional analysis; Cross-section analysis; Cross-sectional shape; Direct metal deposition; Laser scanning velocity; Metallurgical composition; Microstructural analysis; Microstructural coarsening; Asymmetric dilution; Cross-sectional analysis; Metallurgical composition; Microstructure; Rotating direct metal deposition